Unidades fraseológicas especializadas : novas perspectivas para sua identificação e tratamento - Bevilacqua, Cleci Regina (2018)
This paper presents Specialised Phraseologic Units, within the framework of the Terminology’s Communicative Theory (TCT) proposed by Cabré (1998, 1999). First, we will briefly introduce the basic theoretic principles of this theory; we will then discuss the implications of their acceptance for the analysis and treatment of specialised phraseology. Finally, we will mention some of the consequences of this new approach for terminological research in the context of Mercosul.